2016
DOI: 10.1002/jat.3288
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and biomarker evaluation of zebrafish larvae as an alternative model to predict mammalian hepatotoxicity

Abstract: Zebrafish phenotypic assays have shown promise to assess human hepatotoxicity, though scoring of liver morphology remains subjective and difficult to standardize. Liver toxicity in zebrafish larvae at 5 days was assessed using gene expression as the biomarker approach, complementary to phenotypic analysis and analytical data on compound uptake. This approach aimed to contribute to improved hepatotoxicity prediction, with the goal of identifying biomarker(s) as a step towards the development of transgenic model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 55 publications
1
19
0
Order By: Relevance
“…From 5 days post-fertilization (dpf), the liver is indeed functional and expresses enzymes responsible for xenobiotic metabolism that resemble those expressed in humans like cytochrome P450 2E1 (CYP2E1) and alcohol dehydrogenase for alcohol or CYP1A for B[a]P [ 43 , 46 , 47 , 48 , 49 ]. Beside the numerous advantages of zebrafish larva, notably for assessing hepatotoxicant effects [ 50 , 51 , 52 , 53 ], this model has already been demonstrated as very useful for studying fatty liver diseases [ 54 , 55 , 56 , 57 , 58 , 59 ]. In addition, the suitability of this model for studying the involvement of membrane remodeling in chemical-induced liver toxicity has already been reported [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…From 5 days post-fertilization (dpf), the liver is indeed functional and expresses enzymes responsible for xenobiotic metabolism that resemble those expressed in humans like cytochrome P450 2E1 (CYP2E1) and alcohol dehydrogenase for alcohol or CYP1A for B[a]P [ 43 , 46 , 47 , 48 , 49 ]. Beside the numerous advantages of zebrafish larva, notably for assessing hepatotoxicant effects [ 50 , 51 , 52 , 53 ], this model has already been demonstrated as very useful for studying fatty liver diseases [ 54 , 55 , 56 , 57 , 58 , 59 ]. In addition, the suitability of this model for studying the involvement of membrane remodeling in chemical-induced liver toxicity has already been reported [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to human CYP3A, enhanced CYP3A65 transcription in the foregut of the zebrafish larvae in response to dexamethasone and the antibiotic rifampicin confirmed that zebrafish CYP3A65 is an ortholog of the human CYP3A gene (Chang et al, ; Tseng et al, ). CYP3A65 expression in zebrafish has been used as a hepatic biomarker (Al‐Habsi et al, ; Cunha et al, ; Verstraelen et al, ; Xia et al, ) and the zebrafish embryo model was shown to detect hepatotoxicants with higher specificity than the HepG2 cells (Jones et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…They have a small size (1-4 mm) and are easy to maintain, making them cost-effective for an in vivo study. Thus, this model has been successfully chosen to develop a predictive tool for assessing chemical-induced hepatotoxicity with similar effects to those obtained in rodents or human (Sukardi et al, 2011;Hill et al, 2012;Driessen et al, 2013;He et al, 2013;Vliegenthart et al, 2014;Mesens et al, 2015;Verstraelen et al, 2016). Also, it has been increasingly used to study mechanisms of liver injury after acute exposure to a classic hepatotoxicant, alcohol (Passeri et al, 2009;Howarth et al, 2011;Tsedensodnom et al, 2013).…”
Section: Introductionmentioning
confidence: 99%